2012
DOI: 10.1039/c2nr30093a
|View full text |Cite
|
Sign up to set email alerts
|

Industrial graphene metrology

Abstract: Graphene is an allotrope of carbon whose structure is based on one-atom-thick planar sheets of carbon atoms that are densely packed in a honeycomb crystal lattice. Its unique electrical and optical properties raised worldwide interest towards the design and fabrication of future electronic and optical devices with unmatched performance. At the moment, extensive efforts are underway to evaluate the reliability and performance of a number of such devices. With the recent advances in synthesizing large-area graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 148 publications
(227 reference statements)
1
18
0
Order By: Relevance
“…It is likely that the POG lm was folded during the transfer onto the grid. 39 The small particles of high intensity (bright white) dispersed throughout the lm are copper-oxide particles as determined by EDX elemental mapping in Fig. 2b.…”
Section: Resultsmentioning
confidence: 95%
“…It is likely that the POG lm was folded during the transfer onto the grid. 39 The small particles of high intensity (bright white) dispersed throughout the lm are copper-oxide particles as determined by EDX elemental mapping in Fig. 2b.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, transmission electron microscopy (TEM) has been used to demonstrate the atomic structure of graphene [5]. It has been reported that low-energy electron microscopy (LEEM) can be implemented for spatially-resolved measurements of graphene thickness [5]. Although these techniques can provide sufficient insight about the integrity, quality and defects of graphene sheets, they are time consuming and limited to very small scales.…”
Section: Introductionmentioning
confidence: 99%
“…Although these techniques can provide sufficient insight about the integrity, quality and defects of graphene sheets, they are time consuming and limited to very small scales. For industrial applications of graphene, a quick, repeatable and decisive metrology method must be developed to allow characterization of entire area or specific regions of interest of graphene sheets on glass or Si/SiO 2 substrates [5,6]. An alternative for high throughput large-scale characterization of graphene is fluorescent quenching microscopy (FQM) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations